2018
DOI: 10.31603/nursing.v5i1.1876
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Lifestyle Dengan Fungsi Kognitif Pada Lansia

Abstract: An increase in the elderly population as a consequence of an increase in life expectancy.Increasing life expectancy is an indication of the success of long-term development, one of whichimproves both the economic condition and the living standard of society. This increase in lifeexpectancy is related to the changes that occur in the cognitive and mental function of the elderly.Cognitive function in the future is determined by someone’s life experience, health status and lifestyle.This study aims to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…The most common complaint experienced by the elderly is pain, both joint pain and muscle pain. 14 This research is also in line with the study of Reny Chairir et al (2017) showed a positive and significant relationship between cognitive function and physical functional abilities of the elderly. 15 The better the condition of cognitive function, the better the physical functional ability in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…The most common complaint experienced by the elderly is pain, both joint pain and muscle pain. 14 This research is also in line with the study of Reny Chairir et al (2017) showed a positive and significant relationship between cognitive function and physical functional abilities of the elderly. 15 The better the condition of cognitive function, the better the physical functional ability in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…Penelitian ini sejalan yang dilakukan Pinilih (2015), bahwa fungsi kognitif terganggu atau fungsi kognitif berat tertinggi pada usia lansia di atas 75 tahun. Kondisi fungsikognitif pada lansia ini sesuai dengan teoridari Sugarman (2006( , dalam Trihayati, 2016) yang menyebutkan bahwafungsi kognitif menurun di usia tua karenapenurunan jumlah neuron, penurunanukuran otak dan berat otak berkurang.…”
Section: Pembahasan 1 Fungsi Kognitif Pada Lansiaunclassified
“…The life expectancy of women in Indonesia is longer than men. Women who have reached the process of transition from reproductive to old age (also known as senium period) will experience degradation of body organs and physical ability as the process of becoming old (Pinilih, Astuti and Rini, 2018). During the senium period, osteoporosis may occur with different intensities in each woman.…”
Section: Introductionmentioning
confidence: 99%